Co-filtration of bacteria/electrospun oriented carbon nanofibers integrating with carbon nanotubes for microbial fuel cell. Issue 3 (June 2022) - Liu, Yuanfeng; Sun, Yaxin; Li, Huiyu; Ren, Tingli; Lix, Congju
Abstract: Microbial fuel cells (MFCs) provide great potential for recovering electrical energy from waste and inexhaustible biomass. However, inefficient power production and high capital costs still hinder their practical application in large-scale. To address these thorny issues, extensive efforts have been devoted to engineering the anode, mainly on enhancing bacterial loading capacity and extracellular electron transfer (EET) efficiency. Nano-scaffold electrode can satisfy the above merits with large bacteria-accessible surface area and highly conductive network. Yet, the complete utilization of the interior surface for naturally grown bacteria is still challengeable. Herein, the bacteria/electrospun oriented carbon nanofibers integrating with carbon nanotubes (BEO-CNFs/CNTs) was developed as an efficient anode to enhance MFC performance via filtration method. Notably, the BEO-CNFs/CNTs anode greatly enlarged the bacterial loading content and promoted EET efficiency. MFC equipped with BEO-CNFs/CNTs anode achieved a maximum power density of 1016 mW/m 2, which was greatly higher than that of EO-CNFs/CNTs anode with naturally grown biofilm (574 mW/m 2 ) and commercially available carbon cloth (341 mW/m 2 ). Electrochemical results confirmed the superior bioelectrochemical activity of BEO-CNFs/CNTs anode in MFC compared to electrospun oriented carbon nanofibers (EO-CNFs) and electrospun disordered carbon nanofibers (ED-CNFs). The filtration method allowed the c-type cytochromes existed on bacterial outer membrane to have immediate and direct contact to the nanofiber surface for direct electrochemistry, significantly shortening the start-up time of MFC. This study offers a new perspective for preparing efficient anode using electrospinning technology. Graphical Abstract: ga1 Highlights: A novel CNFs composite anode was constructed using electrospinning method. The filtration method enhanced bacterial loading content on EO-CNFs/CNTs. MFCs with BEO-CNFs/CNTs anode greatly shortened the start-up time. The Pmax of BEO-CNFs/CNTs anode was 198% higher than that of commercial CC.